Act of Mar. 26, 1931, No. 225, § 1, Ark. Acts 705-06 - (:unkn) unknown (General Publisher, 1931)
Prohibited the transport from one place to another, or for any railroad, express company, common carrier any firearm of the type commonly known as machine gun.
--
Keywords: MACHINE GUN RESTRICTION